2011
DOI: 10.1590/s0004-28032011000300012
|View full text |Cite
|
Sign up to set email alerts
|

The role of hilar lymphadenectomy in patients subjected to hepatectomy due to colorectal metastasis

Abstract: -Context -Hepatectomy is the treatment of choice for colorectal liver metastases, and several studies have shown good results, with 5-year survival rates ranging from 40% to 57%. Several clinical and pathological predictive factors for survival after liver resection have been studied. Involvement of the hepatic hilum lymph nodes, the incidence of which varies from 2% to 10%, indicates a poor long-term prognosis. Results -Despite variable results, some authors have reported a not-insignificant improvement in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In a recent study [ 36 ], 18% additional lesions were identified in 44% of the patients. At surgery for the resection of CRC liver metastases, concomitant resection of the hepatic hilar lymph nodes is recommended for staging reasons [ 37 ]. Positive hilar lymph nodes can be found in up to 11.5% of patients, and may be associated with unresectability of the liver deposits in 28.6% of the cases [ 38 ].…”
Section: Management Of Resectable Liver Metastases ( Fig 1mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study [ 36 ], 18% additional lesions were identified in 44% of the patients. At surgery for the resection of CRC liver metastases, concomitant resection of the hepatic hilar lymph nodes is recommended for staging reasons [ 37 ]. Positive hilar lymph nodes can be found in up to 11.5% of patients, and may be associated with unresectability of the liver deposits in 28.6% of the cases [ 38 ].…”
Section: Management Of Resectable Liver Metastases ( Fig 1mentioning
confidence: 99%
“…Positive hilar lymph nodes can be found in up to 11.5% of patients, and may be associated with unresectability of the liver deposits in 28.6% of the cases [ 38 ]. Concomitant resection of involved lymph nodes may improve survival [ 37 ].…”
Section: Management Of Resectable Liver Metastases ( Fig 1mentioning
confidence: 99%
“…Regional metastasis to perihepatic lymph nodes is reported to be a significant adverse survival factor for patients with hepatic metastasis from colorectal cancer. [5][6][7] The reported incidence of perihepatic lymph node positivity among individuals undergoing hepatic resection varies from 13 to 50 per cent. [8][9][10] The benefit of routine perihepatic lymph node (HP-LN) during hepatectomy in radiologically-negative patients is unclear.…”
Section: Introductionmentioning
confidence: 99%